"But Problems Dwell so the Urge Is Constant…" Qualitative Data Analysis of the OST CHOICES Program. (20th July 2018) - Shrestha, Umit; Weber, Tess L.; Hanson, Jessica D.
Abstract : Background: Fetal alcohol spectrum disorders are a major public health concern including among American Indian (AI)/Alaska Native (AN) communities. Various studies have demonstrated higher alcohol consumption among AI/AN women during pregnancy compared with other groups. This study intends to understand the milieu within which such consumption patterns flourish. The study utilizes qualitative and quantitative data from the Oglala Sioux Tribe (OST) CHOICES Program, a tribally run public health program that aims to reduce alcohol‐exposed pregnancy preconceptually in AI women. Methods: Alcohol consumption pattern ( n = 264) is analyzed using descriptive statistics. Consumption patterns included average drinks consumed daily, their choice of drinks (beer, whiskey, wine, etc.), how much money participants were spending on alcohol and amount of calories consumed from alcohol. Qualitative data analysis included open coding of data from decisional balance exercise of the CHOICES program that looked at good things and not so good things about participants' drinking. Results: Women reported drinking an average of 12 drinks daily, ranging between 1 and 86. Women drinking at home spent a median of 4, 320 and 12, 960 if drinking at a bar. A median of 1, 200 calories per day from alcohol was reported. More women reported drinking beer compared with other types of alcohol within a domestic setting. Qualitative data analysis identified positive and negative aspects of drinking among the participants of OST CHOICES Program. Positive aspects included escaping from problems, socializing, and relaxation. Negative aspects included impact on families and domestic violence. Conclusions: While understanding their milieu, our study also unraveled different struggles (such as violence, peer pressure, financial burden, and depression) encountered by Native women in their daily lives. According to the participants, positive aspects of drinking outweigh the negative aspects and they viewed their drinking as a solution and not a problem. Abstract : The paper highlights findings of a qualitative data analysis of OST CHOICES intervention among American Indian women who are at risk of alcohol‐exposed pregnancy in South Dakota. Primary motive of the paper is to understand their social milieu that impacts drinking. According to the participants, positive aspects of drinking outweigh the negative aspects and they viewed their drinking as a solution and not a problem. Our analysis also unraveled various struggles faced by the women in their daily lives.